ANALISIS NILAI MORAL DALAM CERITA RAKYAT ASAL USUL NAMA BUKIT MANSIRI DESA GARU KABUPATEN LANDAK - Silvester Izzr Harel; Antonius Totok Priyadi; Sesilia Seli (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to describe the moral values contained in the Folklore of the Origin of the Name Bukit Mansiri, Garu Village, Landak Regency, describe the results of the analysis in the Folklore of the Origin of the Name Bukit Mansiri and design a lesson plan for analyzing moral values in the Indonesian language learning process at the SMA/MA level. The method used is descriptive method in the form of qualitative research. The approach used is the sociology of literature approach. The data source of this research is the Folklore of the Origin of the Name Bukit Mansiri, Garu Village, Landak Regency. The data collection technique used in this research is the technique of observation, interview, recording, recording and data collection tools used are notebooks, pencils, HandPone (HP). The technique of testing the validity of the data uses observation persistence, triangulation and reference coverage. The results of this study are about the moral values contained in the Folklore of the Origin of the Name Bukit Mansiri, Garu Village, Landak Regency. The moral values contained in the Folklore of the Origin of the Name Bukit Mansiri are moral values seen from the relationship between humans and God, moral values are seen from human relationships with humans, and moral values are seen from human relationships with the natural surroundings. The implementation of the moral values contained in the Folklore of the Origin of the Name Bukit Mansiri, Garu Village, Landak Regency for learning Indonesian in terms of curriculum, learning objectives, selection of teaching materials, and in terms of legibility is appropriate as learning material for students in class X SMA/MA.Keywords: Folklore of the Origin of the Name Bukit Mansir, moral values, sociological approach to literature.